2020
DOI: 10.21203/rs.3.rs-17336/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mercury in the terrestrial environment: a review

Abstract: Environmental contamination by mercury is and will continue to be a serious risk for human health. Pollution of the terrestrial environment is particularly important as it is a place of human life and food production. Publication presents a review of the literature on issues related to Hg pollution of the terrestrial environment: soil and plants and their transformations. Different forms of atmospheric Hg may be deposited on surfaces by way of wet and dry processes. These forms may be sequestered within terres… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 106 publications
0
12
0
Order By: Relevance
“…Those are some additional sources of anthropogenic Hg contamination, which can be added to the past mining and coal combustion activities explaining the Hg outliers in Europe (Supplementary Material S4). Thus, we mapped the main 74 chlor-alkali plants using the recent literature reviews on the topic ( Brinkmann et al, 2014 ; Gworek et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Those are some additional sources of anthropogenic Hg contamination, which can be added to the past mining and coal combustion activities explaining the Hg outliers in Europe (Supplementary Material S4). Thus, we mapped the main 74 chlor-alkali plants using the recent literature reviews on the topic ( Brinkmann et al, 2014 ; Gworek et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The main sources of Hg anthropogenic emission are combustion (fossil fuels, municipal and medical waste, sewage sludge, crematories), high-temperature processes (smelting, cement and lime production), manufacturing/commercial, gold extraction, fluorescent lamps and mine spoils ( Huse et al, 1999 ; Mukherjee et al, 2004 ). A recent review has also addressed the Hg emissions close to mining activities and chrol-industries ( Gworek et al, 2020 ). The annual global anthropogenic Hg emissions amount to ~2000–2500 tonnes ( Zhang et al, 2016 ) and outweigh natural emissions (~500 tonnes yr −1 , mainly from rock weathering and volcanic eruptions) ( Amos et al, 2015 ; Bagnato et al, 2015 ) by an order of magnitude ( Futsaeter and Wilson, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…The Żelazny Most flotation waste landfill is the largest of its kind in Europe, and has a negative impact on adjacent ecosystems through wind erosion and transport of pollutants—including trace elements—to both ground and surface waters [ 41 ]. In the case of the Legnica–Głogów Copper Mine District, it has already been reported by Barej et al [ 42 ] that the Hg content in plant material (e.g., grasses and wheat cereals) exceeds those in unpolluted areas (0.1 mg kg −1 according to Gworek et al [ 33 ]); however, the Hg concentrations found did not exceed the levels considered toxic, and the degree of contamination of plant material decreased over the 2002–2017 period [ 42 , 43 ]. The Hg concentrations in pine foliage in the vicinity of the flotation waste landfill in our study, although higher than those reported for the rest of Poland, also do not pose a threat to the environment.…”
Section: Discussionmentioning
confidence: 99%
“…Although Hg content in Scots pine foliage in Poland did not exceed the values found in ecosystems outside industrial emission areas, this study examined the spatial variation in mercury content across the country. According to Gworek et al [ 33 ], plants growing beyond the influence of high Hg emissions had less than 0.1 mg kg −1 Hg. Higher Hg concentrations in pine foliage were found in areas affected by industrial pollution, including in the catchment area ~20 km from a lignite power plant in Spain (average 0.060 mg kg −1 ) [ 34 ], and the area around a chloralkali plant in the Czech Republic (from 0.0202 mg kg −1 in the plant’s low-impact zone, up to 0.0615 mg kg −1 in the high-impact zone) [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…The only other metal with a BAF above one was Co indicating a higher mobility rate of these two metals according to Aladesanmi et al (2019). Hg is a known toxic, persistent and mobile contaminant that has been listed as one of the 10 leading chemicals of concern (Gworek et al, 2020) and as one of the three most toxic elements on the planet (Rice et al, 2014). Given that Hg has the potential to biomagnify up trophic levels (Seco et al, 2021) the presence of Hg in the e‐waste soils, even at low concentrations observed in this study, is a cause for concern.…”
Section: Discussionmentioning
confidence: 99%